The demography, breeding biology and management of two mullet species (Pisces : Mugilidae) in the Eastern Cape, South Africa - Bok, Anton (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1984)
Aspects of the life history of Myxus capensis which were likely to be most affected by man-induced habitat changes, were studied in the eastern Cape. Myxus capensis was found to be specialized for a catadromous life history. The fry migrate into freshwater reaches of rivers within a few months of being spawned at sea and return to an estuarine or marine environment when maximum size has been attained and large energy reserves necessary for spawning have been accumulated. Myxus capensis penetrates considerable distances up eastern Cape rivers and although present in the upper reaches of some estuaries, is only common in freshwater-dominated systems. Myxus capensis has adapted its life history style in a number of ways to overcome the constraints associated with the spatial separation of the freshwater feeding areas and the marine spawning grounds in a region prone to droughts and erratic river flow. Research on the more estuarine-dependent Mugil cephalus, which is also found in the freshwater reaches of eastern Cape rivers, enabled useful comparisons to be drawn. As the latter species is not dependent on a freshwater phase in its life cycle, it is subject to different selection pressures. This comparative approach gave insights into the adaptive significance of the life history tactics of Myxus capensis. Myxus capensis displays a number of life history tactics characteristic of migratory fish species which are thought to increase population fecundity by increasing the number of large females and hence maximizing egg production. These include a sex ratio in favour of females, faster female growth, females remaining longer in the freshwater feeding areas and reaching a larger ultimate size. Possible adaptations to the periodic isolation of the feeding and spawning areas include: (i) the development of ripe gonads only in estuarine or marine areas when access to the spawning grounds is ensured; (ii) year-round spawning and hence recruitment which enables the erratic floods to be used at any time for downriver spawning migrations and reduces the chances of total recruitment failure due to short-term adverse environmental conditions and (iii) a relatively wide range of size and age at first (and final) sexual maturity (2+ to 5+ years); this tends to ensure successful reproduction and recruitment in spite of a series of poor years, as well as dampen population fluctuations after long periods of isolation in fresh water. The dependence of Myxus capensis on the freshwater reaches of eastern Cape rivers makes this species vulnerable to man-induced habitat changes. The erection of barriers to migration has cut off large stretches of suitable habitat and almost completely eliminated Myxus capensis from certain rivers. This detrimental effect has been largely responsible for the recent inclusion of this species on the Red Data list of endangered fish species in South Africa. This study demonstrated the considerable fisheries potential of both mullet species and this should ensure that their conservation and wise utilization be given high priority. Management proposals include: (i) the netting and lifting of Myxus capensis over barriers to migration; (ii) the construction of fish ladders when feasible and (iii) the artificial propagation of this species to enable large-scale stockings of existing man-made impoundments as well as natural habitats to be carried out. It is predicted that the life history characteristics of Myxus capensis, which evolved in response to an erratic freshwater environment, should ensure that when man-induced habitat changes are rectified, this species will again flourish in eastern Cape rivers.
Keywords: Fishes -- South Africa -- Eastern Cape; Mullidae -- South Africa -- Eastern Cape; Estuarine ecology -- South Africa -- Eastern Cape